Optical Characteristic Properties of Probiotic Drink Using Spectrophotometer UV/Vis and FTIR. (August 2019) - Sitorus, Rizqa; Herman,; Hendro,
Abstract: This research aims to qualitively observe the light absorbtion response from probiotic drink to several spectra of electromagnetic waves. This absorption response will later be related to physical properties of probiotic drink. The Observations in the infrared region used Bruker ATR Alpha FTIR Spectrometer while the observations in the UV and visible light region used Thermo Scientific Evolution 220 UV-Visible Spectrophotometer. The measuring time was done until there is a change in probiotic drink absorption. The measurement results obtained were in the form of the transmittance spectrum of the wavelength. Measurements in the infrared region showed some probiotic drink content such as protein at 6123 nm, lactose at ∼9532 nm, and glucose at wave number ∼1100-800 cm −1 . In the UV region, it is related to the reduction amount of protein while visible light region was associated with changes in the constituent particles of probiotic drink along with changes in pH. All observations refer to the literature. The results of this observation certainly do not represent all the contents of probiotic drink but this method can also be utilized for freshness detection of other similar drinks that contain milk.